Antiphospholipid syndrome – what’s new? - Szczepaniak, Elżbieta; Osmola, Agnieszka; Prokop, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Antiphospholipid syndrome is characterized by the presence of heterogenous group of antibodies for which cofactors are β2 glicoprotein-1 (β2 GP I), protrombin, proteins S and C, thrombomodulin and anexin. Clinical picture strictly depends on diameter and type of vessels thrombosis (capillary vessels, veins, arteries) of skin, internal organs or brain. Characteristic symptoms include recurrently obstetrics outcome and thrombocytopenia. The role of phospholipids binding proteins – β2-GPI as autoantigens in pathogenesis of antiphospholipid syndrome is recently often discussed.